THE THE ACTS OF KUALA LANGAT COMMUNITY LEARNING CENTER MALAYSIA TEACHERS TO OVERCOME LEARNING DIFFICULTIES AMONG STUDENTS - Putri Rahmawati, Nadia; Utami, Ratnasari Dyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
Previous studies proved that Flash Cards is beneficial in learning English vocabulary. However, comparing the young learners’ perspectives about the implementation of this media in two different context is still limited. The research aims to explore how young learners perceived the use of Flash Cards as a learning medium in learning English in two different cultural background. The participants included 8 students from Sanggar Bimbingan in Malaysia and 41 students from an elementary school in Waru, Indonesia, spanning grades 4 through 6. Data of the research were collected through giving questionnaires and interviewing the elementary school students. The findings suggest that incorporating flashcards into the learning process is an effective strategy for improving students' English vocabulary. The study anticipates that this approach will lead to increased student engagement and activity in English learning, providing them with more opportunities to practice vocabulary and sentence structures within real-life contexts. By utilizing Flash Cards, students are expected to engage more actively in practicing various vocabulary and sentence structures, enhancing their English language skills. This research encourages teachers to integrate this medium into their classrooms, making lessons enjoyable, comprehensible, and innovative in bolstering students' vocabulary.